Risk management procedures for physical development projects in the Ministry of Education - Ahmad Salleh, Mazlina (2015)
This research is focused on the importance of Risk Management (RM) to be implemented in the Ministry of Education (MOE) and aims to identify the level of problems of the current practice as well as level of awareness towards RM in MOE. Apart from that, it also aims to examine the relationship of RM implementation towards successful process of project management in Jabatan Kerja Raya (JKR). Questionnaire and interview sessions were carried out in order to obtain a better view on the above situations. It was found that the level of problems with the current practice is at moderate level thus contributed to the awareness of having RM to be implemented. A survey done in JKR also shows that RM does influence the smoother process of project management. Based on the findings of both tools, important phases of project management were also determined and contributed to the drafting of the proposed format of RM Procedure. It can be concluded that RM is important to be implemented as JKR did, thus MOE should consider implementing it to reduce issues in managing project by starting with the format propose.